Lipid Oxidation Derived Aldehydes and Oxysterols Between Health and Disease. Issue 1 (26th April 2018) - Sottero, Barbara; Leonarduzzi, Gabriella; Testa, Gabriella; Gargiulo, Simona; Poli, Giuseppe; Biasi, Fiorella
Abstract : Non‐enzymatic and enzymatic oxidation of lipids has long been a primary issue in human pathophysiology, with special emphasis on diet‐ and nutrition‐related aspects. While there is no doubt that the n‐3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid, and docosahexaenoic acid, exert anti‐inflammatory, inflammation resolving, and immunomodulatory effects in different model systems, their non‐enzymatic oxidation during food storage and cooking, as well as during gastrointestinal digestion, can give rise to excessive amounts of quite reactive aldehydic end‐products, in particular 4‐hydroxyhexenal. However, the non‐enzymatic oxidation of n‐6 PUFAs is, in principle, far more harmful, not least because one of its main end‐products, 4‐hydroxynonenal, has been shown to be associated with the progression of a number of human diseases. Several cholesterol oxidation products, known as oxysterols, are also of primary nutritional importance; these can be generated in the human body through both enzymatic and non‐enzymatic reactions, but may also be present in the diet in excessive amounts due to the autoxidation of cholesterol‐containing foods. Their potential contribution to the pathogenesis and progression of human diseases in which hypercholesterolemia is a primary risk factor, such as atheroclerosis, Alzheimer's disease, and some forms of cancers, has been unanimously recognized. Practical Applications : This review highlights the importance of certain lipid oxidation products, namely 4‐hydroxyalkenals and oxysterols, in the modulation of processes fundamental to human health and disease. The observations and facts reviewed here underline the need to carefully consider the pros and cons of the dietary intake and metabolic fate of n‐3 PUFA, n‐6 PUFA, and cholesterol, when producing, storing, and processing lipid‐containing food. Lipid oxidation is a common process that occurs through both enzymatic and non‐enzymatic reactions . It is responsible for the formation of several compounds, including polyunsaturated fatty acid (PUFA)‐derived 4‐hydroxyalkenals and cholesterol oxidation products, namely oxysterols. Depending on their concentrations, these molecules possess physiopathological properties involved in cell viability and function. At high concentrations, such as those resulting from intense oxidative stress or excessive fatty food intake, they are associated to the onset of many diseases. A correct diet regimen, improved food processing and storage, and suitable antioxidant supplementation, should be implemented to counteract promotion of disease development by excess oxidized lipids. (HHE, 4‐hydroxyhexenal; HNE, 4‐hydroxynonenal; ROS, reactive oxygen species). Abstract : Lipid oxidation is a common process that occurs through both enzymatic and non‐enzymatic reactions . It is responsible for the formation of several compounds, including polyunsaturated fatty acid (PUFA)‐derived 4‐hydroxyalkenals and cholesterol oxidation products, namely oxysterols. Depending on their concentrations, these molecules possess physiopathological properties involved in cell viability and function. At high concentrations, such as those resulting from intense oxidative stress or excessive fatty food intake, they are associated to the onset of many diseases. A correct diet regimen, improved food processing and storage, and suitable antioxidant supplementation, should be implemented to counteract promotion of disease development by excess oxidized lipids. (HHE, 4‐hydroxyhexenal; HNE, 4‐hydroxynonenal; ROS, reactive oxygen species).